2021
DOI: 10.1186/s12891-021-04273-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lumbar spinal stenosis on bone mineral density in osteoporosis patients treated with ibandronate

Abstract: Background Lumbar spinal stenosis (LSS) can cause various neurological symptoms and reduce the daily activity of patients. Many studies have shown that free physical activities and exercise can improve bone mineral density (BMD) in patients with osteoporosis. However, the effect of LSS on BMD has not been reported. The purpose of this study was to investigate the effects of LSS on BMD in patients treated with ibandronate for newly diagnosed osteoporosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study by Kim et al [ 32 ] showed a higher bone turnover rate in patients with spinal stenosis. In a case-control study, Park et al [ 33 ] suggested that patients with spinal stenosis are less likely to benefit from ibandronate treatment compared with the control group. The neurological claudication caused by spinal stenosis could lead to reduced strength in the lower extremities and a higher bone loss rate [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kim et al [ 32 ] showed a higher bone turnover rate in patients with spinal stenosis. In a case-control study, Park et al [ 33 ] suggested that patients with spinal stenosis are less likely to benefit from ibandronate treatment compared with the control group. The neurological claudication caused by spinal stenosis could lead to reduced strength in the lower extremities and a higher bone loss rate [ 34 ].…”
Section: Discussionmentioning
confidence: 99%